Improvement of the Nursing Care Organization Model in Palliative Care: A Comprehensive Analysis of Optimization and Digitalization Pathways (KIUT Publication, 2025)
Palliative care is aimed at comprehensively alleviating suffering and improving the quality of life for patients with severe and chronic illnesses, as well as supporting their families. In this system, nursing care plays a central role by providing symptom control, psycho-emotional support, and coordination of a multidisciplinary team. However, modern nursing care models often face challenges related to limited resources and staffing, lack of clear protocols, and high emotional burden.